The application of an atypical neural network when quantifying the modeling of environmental aspects - Jovanović, Jelena (Strojniški vestnik, 2006)
This paper looks at the environmental aspects' quantification phase, where a new method based on a neural network was initiated. The method should provide sufficient objectivity and accuracy in the assessment of environmental impacts for all types of organization, and it is based on the specificity of available mathematical models used by certified organizations in Serbia & Montenegro.
Keywords: mreže nevronalne; zaščita okolja; vidiki okoljski; vplivi okolja; vrednotenje; nevronske mreže; okolje; natural environment; modeliranje